Hierarchical filters determine community assembly of urban species pools. Issue 11 (3rd November 2016) - Aronson, Myla F. J.; Nilon, Charles H.; Lepczyk, Christopher A.; Parker, Tommy S.; Warren, Paige S.; Cilliers, Sarel S.; Goddard, Mark A.; Hahs, Amy K.; Herzog, Cecilia; Katti, Madhusudan; La Sorte, Frank A.; Williams, Nicholas S. G.; et al.
Abstract: The majority of humanity now lives in cities or towns, with this proportion expected to continue increasing for the foreseeable future. As novel ecosystems, urban areas offer an ideal opportunity to examine multi‐scalar processes involved in community assembly as well as the role of human activities in modulating environmental drivers of biodiversity. Although ecologists have made great strides in recent decades at documenting ecological relationships in urban areas, much remains unknown, and we still need to identify the major ecological factors, aside from habitat loss, behind the persistence or extinction of species and guilds of species in cities. Given this paucity of knowledge, there is an immediate need to facilitate collaborative, interdisciplinary research on the patterns and drivers of biodiversity in cities at multiple spatial scales. In this review, we introduce a new conceptual framework for understanding the filtering processes that mold diversity of urban floras and faunas. We hypothesize that the following hierarchical series of filters influence species distributions in cities: (1) regional climatic and biogeographical factors; (2) human facilitation; (3) urban form and development history; (4) socioeconomic and cultural factors; and (5) species interactions. In addition to these filters, life history and functional traits of species are important in determining community assembly and act at multiple spatial scales. Using these filters as a conceptual framework can help frame future research needed to elucidate processes of community assembly in urban areas. Understanding how humans influence community structure and processes will aid in the management, design, and planning of our cities to best support biodiversity.